The Governance of Ex-Indonesian Migrant Workers Empowerment Based on Entrepreneur Skill in Malang - Mindarti, Lely Indah; Nabila, Putri; Rosalinda, Henny; Yustiari, Shinta Happy (Institut Agama Islam Negeri Madura, 2022)
This study aims to understand the process of ex-Indonesian migrant workers’ empowerment through the Productive Migrant Village (Desmigratif) program in Arjowilangun Village. In this study, the writers use a qualitative approach because they want to directly observe the empowerment of ex-Indonesian migrant workers (PMI) in Arjowilangun Village. The research type used in this study is a case study. The data collection techniques are observation, interview, and documentation. Desmigratif program has several focused activities. One of them is to develop productive businesses. These productive business activities aim to help the growth of the entrepreneurship spirit of ex-Indonesian migrant workers and improve their confidence and welfare. The purposes and the main focuses of this study are to know and to decipher as follows: (1) various efforts that are done in the empowerment of ex-Indonesian migrant workers through productive business activities; (2) various factors that can support and detain the effort of ex-Indonesian migrant workers’ empowerment in Arjowi-langun Village. The result of this study shows that Desmigratif Program in Arjowilangun Village has run well. Still, the empowerment process of ex-Indonesian migrant workers in Arjowilangun Village is not yet maximum. It is caused by the lack of capital assistance in productive business activities and the minimum knowledge of ex-Indonesian migrant workers about marketing.